Clases virtuales y su repercusión en el comportamiento y estado mental de un adolescente de 13 años - Duarte Rodríguez, Génesis Narcisa (2021)
Since the closure of educational units due to COVID-19, adolescents have had to work virtually, influencing their behavior as well as their mental health, changing physical contact and attendance to establishments for student applications (app) and connectivity, which have become the essential tool to support learning. The present research focuses on analyzing the impact of virtual classes on the behavior and mental state of an adolescent due to the situation that the country and the world are going through, forcing people to comply with rules and restrictions in order to avoid the spread of the pandemic due to COVID-19 ,in this study it is essential to emphasize the lines of research of the Psychology career such as prevention and diagnosis and as a sub-line of research, behavioral disorder and its impact on the teaching-learning process. To carry out the research, techniques such as Observation, Interviews, Clinical History and Psychometric tests are used to design the psychotherapeutic scheme, being this the plan that will be used to work with the patient. The justification details the contribution, importance, viability, beneficiaries and feasibility of this research, making reference to the repercussions that virtual classes have on the behavior and mental health of a 13-year-old adolescent. After all the aforementioned process, the conclusions, recommendations and bibliographies are presented.